Прогнозування та ймовірносна оцінка довговічності технічних об’єктів - Fedin, S. S. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
Based on the methodology of the Markov analysis, a probabilistic approach to forecast and estimation of the longevity of technical objects is offered. A mathematical model of the longevity forecast is developed with the use of statistical data characterizing the initial and final distribution of the service term of technical objects.